The textual tradition of the Gospels : Family 1 in Matthew - Anderson, Amy S. (New Testament tools and studies, 2003)
This investigation of the 10th century minuscule Codex 1582 in the Gospel of Matthew includes a description of the physical document and an extensive evaluation of the text it contains. The manuscript was copied by the monk Ephraim, who is known to scholars in various fields. The high quality of his work and of the documents which were available to him demonstrate that he carefully reproduced an exemplar which witnessed to an ancient and valuable text. The text and marginal variants of Codex 1582 are shown to be related, though not identical, to the text of Matthew used by Origen, raising the possibility of a Caesarean archetype. A full collation of Codex 1582 to Codex 1 demonstrates that 1582 should be the leading member, as well as the basis for the age and readings of Family 1 in Matthew. Test collations of twelve other supposed family members lead to a re-evaluation of the interrelationships of the documents and an expanded stemma of the family.